GUcal: An integrated application for capillary electrophoresis based glycan analysis. Issue 24 (8th October 2015) - Jarvas, Gabor; Szigeti, Marton; Guttman, Andras
Abstract : Recent emergence in the use of monoclonal antibody therapeutics and other glycoprotein biopharmaceuticals requires high‐throughput, robust, and automated techniques for their glycosylation analysis. Capillary electrophoresis is one of the high‐performance methods of choice; however, while the necessary instrumentation is well developed, the related bioinformatics tools are lacked behind. In this paper, we introduce an integrated toolset dubbed as GUcal, to automatically calculate the glucose unit (GU) values for all sample components of interest in an electropherogram with a concomitant database search for structural assignment. The database comprises CE GUs and suggested structures of N ‐glycans released from human IgG. The app is freely available online (www.lendulet.uni‐pannon.hu/gucal ) and readily facilitates CE‐based glycan analysis.